Business Driven Information Systems - Baltzan, Paige (McGraw-Hill, 2025)
Business Driven Information Systems discusses various business initiatives first and how technology supports those initiatives second. The premise for this unique approach is that business initiatives should drive technology choices and provide the foundation that will enable students to achieve excellence in business, regardless of their major. The text is available with Connect, McGraw Hill's course management and adaptive learning system, helping millions of students reach their potential every year. The new 8th edition is state of the art in its discussions, presents concepts in an easy-to-understand format, and allows students to be active participants in learning. By engaging students with numerous case studies, exercises, projects, and questions that enforce concepts, Business Driven Information Systems creates a unique learning experience for both faculty and students.